ENHANCING PRODUCTION STANDARDS, PRODUCT INNOVATION, AND MARKET COMPETITIVENESS OF SOLAR-DRIED FISH RINGS USING A DESIGN THINKING APPROACH: A CASE STUDY OF COMMUNITY-BASED ENTERPRISES IN SIRINDHORN DISTRICT, UBON RATCHATHANI PROVINCE, THAILAND. - Boonthawee, Kittawat; Wanna, Ananya; Nanta, Sukanlaya; Chotivanich, Piyakanit; Suntramethakul, Anan; Kruasom, Taisith (Scientific Culture, 2025)
This study explores exciting strategies to boost the production and commercial potential of solar-dried fish rings, crafted by community-based enterprises (CBEs) in the vibrant Sirindhorn District of Ubon Ratchathani, Thailand. By utilizing a Design Thinking framework, it actively engaged stakeholders to tackle operational and market challenges with four key goals: (1) standardizing production processes for even better quality, (2) creating a crispy fried fish ring variant that delights consumer preferences, (3) introducing sustainable packaging to help extend shelf life, and (4) leveraging popular digital platforms like Facebook and Shopee to broaden market reach. The key results showcased significant improvements in both production and marketing. Standardized processes not only enhanced product consistency but also revealed through nutritional analysis that the fish rings have a high protein content. Innovations in sustainable packaging, including laminated aluminum foil, beautifully doubled the product's shelf life while addressing environmental concerns. Digital marketing initiatives increased online sales by 20% within just three months, enhancing visibility and boosting revenue. Moreover, process optimization and cost-effective packaging managed to lower production costs by 24.08%, further enhancing profitability and competitive pricing. Overall, these findings illustrate how effective Design Thinking can be in overcoming challenges faced by CBEs, providing a scalable model for innovation, sustainability, and resilience. This thoughtful approach empowers rural enterprises for lasting success in everchanging markets, encouraging economic empowerment and fostering environmental stewardship in local communities.